A radiation hard bandgap voltage reference for the ARCADIA project. (1st January 2023) - Traversi, G.; Falchieri, D.; Gaioni, L.; Manghisoni, M.; Pezzoli, M.; Ratti, L.; Re, V.; ,
Abstract: This work presents the design and characterization results of a radiation hard bandgap reference circuit fabricated in a 110 nm CMOS technology for the Main Demonstrator chip of the ARCADIA project. The design, based on a current-mode approach in order to be able to output a smaller than 1.2 V reference voltage, employs diode-connected MOSFETs instead of BJTs to enhance the radiation hardness and a second amplifier to improve the current mirror of the output branch and therefore the line regulation of the circuit. This paper describes the features of the circuit and its measured results.